Penerapan Aplikasi Program Linear Dengan Menggunakan Metode Simpleks Untuk Mendukung Kegiatan UMKM - Rinna Rachmatika (STMIK Budi Darma, 2022)
UMKM are individual businesses that can be managed by anyone, such as housewives, millennials, and parents. During the Covid-19 pandemic, many people were affected by termination of work contracts or layoffs, so many of them opened small businesses. Which turned out to be, the economy in Indonesia during the Pandemic was helped because of these UMKM actors. Warung Dominasi is an UMKM engaged in the chicken-based food industry. Orders can be made by pre-order and now they have opened a store in the canteen of the Pamulang University. It's just that, these UMKM are still unable to carry out production planning so that sometimes the profits are not in accordance with the capital that has been spent. Production planning must of course be carried out by business actors, such as designing a product strategy, or thinking about the type of goods to be produced. Linear programming is a method for obtaining optimal results from a mathematical model composed of linear relationships. The Simplex method is an iterative mathematical strategy (repetition), the simplex technique can be used to deal with problems where there are two or more decision variables. The results obtained by applying this method help UMKM in planning production according to the decisions and available resources.